A campus on the move: Modal choices of students and staff at the University of Lausanne, Switzerland. (December 2021) - Rérat, Patrick
Highlights: Transport represents a core challenge for the attractiveness of universities and their ecological footprint. 13 surveys address the mobility practices at the University of Lausanne, Switzerland. The majority of the university community use public transport, which is explained by investments in infrastructures and the quality of the offer. Modal choices are influenced by gender, age, income, territorial context but also values as reflected by differences between faculties. Mobility policies have drawn on the development of public transport, the restriction in car parking and the staggering of the start time of classes. Abstract: Universities generate significant transport flows on a daily basis. Transport represents a core challenge for the attractiveness of universities but also for their ecological footprint. This paper addresses the mobility practices of students and staff at the University of Lausanne, Switzerland, through a series of 13 annual surveys. The majority of the university community use public transport, which is explained by investments in infrastructures, the development of their carrying capacity (frequency and size of vehicles) and also the staggering of the start time of classes that has flattened peak hours. The efficiency of public transport and a parking policy have more than halved the modal share of the car. Cycling has experienced a notable growth unlike motorized two-wheelers and walking. The paper then addresses how mobility practices diverge within the university community. Modal choices can be explained when the effects of gender, age, income, territorial context (distance and mobility offer) but also values (as reflected by several differences between faculties) are looked at together. Overall, the paper brings knowledge to the issue of mobility on university campuses and the levers that could turn them into sustainable communities.